2016
DOI: 10.1016/j.psychres.2016.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for DSM-5 nonsuicidal self-injury in female adolescent inpatients: The role of childhood maltreatment, alexithymia, and dissociation

Abstract: The purpose of this study was to examine the relationship between various adverse childhood experiences, alexithymia, and dissociation in predicting nonsuicidal self-injury (NSSI) in an inpatient sample of female adolescents. Seventy-two adolescents (aged 14-18 years) with NSSI disorder (n=46) or mental disorders without NSSI (n=26) completed diagnostic interviews and self-report measures to assess NSSI disorder according to the DSM-5 criteria, childhood maltreatment, alexithymia, and dissociation. Alexithymia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…Several studies using the TAS and the TAS-20 scales reported higher internal consistency of the TAS-20 [37]. Taking into account that the German version of the TAS had higher reliability, notably for the EOT factor, than the TAS-20, Lüdtke et al [38] have used the TAS in a sample of 72 female patients aged 14–18 years. The TAS had satisfactory reliabilities with a value for the Cronbach alpha coefficient of 0.81 and 0.67 for the full scale and the EOT factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using the TAS and the TAS-20 scales reported higher internal consistency of the TAS-20 [37]. Taking into account that the German version of the TAS had higher reliability, notably for the EOT factor, than the TAS-20, Lüdtke et al [38] have used the TAS in a sample of 72 female patients aged 14–18 years. The TAS had satisfactory reliabilities with a value for the Cronbach alpha coefficient of 0.81 and 0.67 for the full scale and the EOT factor.…”
Section: Discussionmentioning
confidence: 99%
“…It would seem that alexithymia in adolescents moderated, and partially mediated, the relationship between bullying and deliberate self-harm [3]. In female adolescents, multivariate logistic regression analyses indicated that only alexithymia (and not dissociation or childhood maltreatment) was a significant predictor for non-suicidal self-injury [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Although we found that the link between emotional dysregulation and NSSI was robust across participants from various countries, such as the United States [42,51], Canada [59][60][61], Italy [52], Germany [55][56], New Zealand [62][63], and the Netherland [57], these countries are all western countries and participants in these studies were predominantly identified as Caucasian. Only two studies being reviewed involved non-western samples: one involved Turkish [38], and the other Japanese [64].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The combination of emotional dysregulation with these NSSI specific vulnerability factors may increase the likelihood of engaging in NSSI among clinical samples. Additionally, these results may be explained by cautions due to that the studies with clinical samples involve a variety of patient populations, including substance-dependent patients [38,[50][51][52], anxiety disorder patients [50,53,54], eating disorder patients, depressive disorder patients [53,55], and NSSI patients [56,57], etc. So the comorbid (psychiatric) conditions may contribute (directly or indirectly) to NSSI, and may thus confounding the study's association.…”
Section: Research Min-pei Lin Jianing Youmentioning
confidence: 99%
“…Using a meta-analytic approach to identify risk factors for NSSI, previous NSSI, hopelessness, Cluster B symptoms and prior suicidal thoughts or attempts were identified as strongest risk factors [18]. From an inpatient sample of 72 female adolescents alexithymia was identified as risk factor for NSSI according to DSM 5 diagnosis [19]. It seems that NSSI itself is also a risk factor, not only for recurrent NSSI (as stated above), but also for interpersonal stressful life events, with the frequency of NSSI predicting the number of interpersonal stressors among girls [20].…”
Section: Introductionmentioning
confidence: 99%